Utilising SATA in Measuring Students’ Understanding of Financial Statements: A Survey among Non-Accounting Students - Shamsudin, Adriana; Mohd Pauzi, Nur Farahah; Karim, Mohd Syazwan; Roslan, Nurfarahin; Ahmad, Khairiah (Jurnal Dinamika Akuntansi, 2020)
Accounting is perceived as a complicated process due to its technical difficulties. However, accounting knowledge is undeniable essential to complete a business plan. The Ã¢â‚¬ËœSimplified Accounting Template for ApprenticeÃ¢â‚¬â„¢ (SATA) is developed to facilitate students especially non-accounting students who have very little accounting knowledge in preparing proforma financial statements at the financial section in the business plan. SATA act as integral part of technology used in accounting education to improve studentsÃ¢â‚¬â„¢ understanding on accounting and help them to complete the business plan. The objective of this paper is to access the level of studentsÃ¢â‚¬â„¢ understanding on accounting with the introduction of SATA in teaching and learning which finally can assist them to prepare financial statements. A hands-on workshop was conducted by accounting lecturers in UiTM Malacca Branch Jasin Campus on SATA to assist the students in completing the business plan for financial section. A questionnaire was given at the end of the workshop to the students to gather their feedback related on SATA and give their perceptions using SATA in preparing financial statements. This study found that more than 80% respondents admitted that SATA improved their understanding on accounting terms such as terms of non-current assets, non-current liabilities, sales, purchases, 85% agreed that SATA took lesser time to prepare financial statements, 90% found that SATA was very easy to use as compared to manually prepared the financial statements and facilitates in analyzing financial performance and 91% agreed that SATA really help them in completing their business plan particularly in financial section. On overall most of respondents admitted that SATA increase their understanding in preparing financial statements. This study also revealed that most of the respondents understand the component of Statement of Profit or Loss and Statement of Financial Position embedded in SATA.Ã‚Â